A Soft, Fast and Versatile Electrohydraulic Gripper with Capacitive Object Size Detection. (11th November 2022) - Yoder, Zachary; Macari, Daniela; Kleinwaks, Gavriel; Schmidt, Ingemar; Acome, Eric; Keplinger, Christoph
Abstract: Soft robotic grippers achieve increased versatility and reduced complexity through intelligence embodied in their flexible and conformal structures. The most widely used soft grippers are pneumatically driven; they are simple and effective but require bulky air compressors that limit their application space and external sensors or computationally expensive vision systems for pick verification. In this study, a multi‐material architecture for self‐sensing electrohydraulic bending actuators is presented that enables a new class of highly versatile and reconfigurable soft grippers that are electrically driven and feature capacitive pick verification and object size detection. These electrohydraulic grippers are fast (step input results in finger closure in 50 ms), draw low power (6.5 mW per finger to hold grasp), and can pick a wide variety of objects with simple binary electrical control. Integrated high‐voltage driving electronics are presented that greatly increase the application space of the grippers and make them readily compatible with commercially available robotic arms. Abstract : This study presents a new type of electrohydraulic, multi‐material soft gripper that uses an active continuum structure simultaneously as an actuator and a sensor, allowing for grasp detection and object size estimation. The gripper is fast, modular, and robust; using only simple controls inputs it can grip a wide variety of objects, including delicate fruits, without inflicting damage.